Energy and nutrient consumption in Mexican women 12-49 years of age: Analysis of the National Nutrition Survey 1999 - Juan Espinosa (Salud Pública de México, 2003)
Objective. To describe the reported energy and nutrientintake and adequacies in Mexican women. Material andMethods. A 24-hour dietary recall was used to obtain nutrientintake in a representative sub-sample of 2 630 womenfrom 12 to 49 years of age from the National NutritionSurvey 1999. Nutrient adequacies were estimated using theDietary Reference Intakes and stratified according to region,area (urban or rural), socioeconomic status and obesitystatus (non-obese: BMI <30 kg/m2, obese: ³30 kg/m2).Differences were analyzed using linear regression for complexsurveys of log-transformed intake and adequacy, adjustingfor multiple comparisons with the Bonferroni test.Results. The median national energy intake was 1 471 kcal.The Risk of Inadequacy (RI) (prevalence of adequacy <50%)was: vitamin A:38.3%, vitamin C: 45.5%, and folate: 34.3%.Carbohydrates, folate, iron and calcium intake was significantlyhigher in rural than in urban areas. The RI was higherin women of the lowest socioeconomic status tertile for allnutrients with the exception of carbohydrates and calcium.Macro-nutrient adequacies were significantly higher in nonobesewomen. Conclusions. Differences within the countryamong regions, rural and urban areas, and socioeconomicstatus tertile reflect an increasing availability of inexpensivecalorie-dense foods in marginal groups. However, total energy,cholesterol, saturated and total fat were consumed ingreater quantities by women from the higher socioeconomicstatus tertile and from urban areas. These patterns could be a contributing factor to the rise of obesity and other noncommunicablenutrition-related chronic diseases in Mexico.The English version of this paper is available at: http://www.insp.mx/salud/index.html